Amortization Analysis Of Toll Road Concession Assets After The Implementation Of Pmk 72 Of 2023 And Its Effect On Financial Statements - Ghea Ernanda Hapsari; Akie Rusaktiva Rustam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This qualitative case study examines changes in fiscal amortization policy for toll road concession rights assets following the implementation of Minister of Finance Regulation (PMK) Number 72 of 2023, using PT XYZ, a company in the toll road management sector, as the case study. The regulation introduces an alternative for determining the useful life of intangible assets: either the fourth asset group’s useful life (20 years) or the actual useful life based on the company’s accounting records. PT XYZ opted to align its fiscal amortization with the actual useful life, replacing its previous policy. This study uses primary and secondary data obtained through triangulation techniques, including interviews, observations, and document analysis. The analysis, conducted using the Miles and Huberman model, shows that the change in amortization policy reduced fiscal amortization expenses by 57%, resulting in a decrease in temporary differences from IDR 57.2 billion to IDR 13.5 billion. This led to a 702% increase in fiscal profit and a 76% decrease in deferred tax. These effects significantly influence the company’s current-year profit, equity, and liabilities. This study fills a gap in the literature by providing empirical insight into the regulatory implications for accounting and taxation practices in the toll road sector.